Design and simulation of an adjustable high voltage DC-DC converter - Ng, Rui Qi (2017)
A Flyback DC-DC converter capable of boosting an input voltage of 5V to an output voltage ranging from 30-300V with a 5mA load is presented. The output voltage is also customised to be electronically tunable, with a user-defined input. Due to the space constraints involved, the Flyback transformer utilised in this project is small, with a primary-secondary inductance ratio of 20µH : 2mH. The off-chip capacitance is also kept to a minimal value of 220nF. Due to the small inductance value, the Flyback converter operates in the discontinuous conduction mode. The Flyback converter uses the current-mode control, which serves to provide some form of voltage-feedforward (on top of the conventional voltage-feedback) in anticipation of sudden line changes thus providing excellent dynamic response. The on-chip current-mode controller is being implemented in CSM130nm technology. An efficiency of 90% is achieved under the most ideal conditions where the coupling coefficient between the primary and secondary coil, M, is unity. An efficiency of 70% is achieved when M is 0.87.